Asoprisnil as a Novel Ligand Interacting with Stress-Associated Glucocorticoid Receptor - Ovinuchi Ejiohuo; Donald Bajia; Joanna Pawlak; Aleksandra Szczepankiewicz (Biomedicines)
Background/objective: The glucocorticoid receptor (GR) is critical in regulating cortisol production during stress. This makes it a key target for treating conditions associated with hypothalamic–pituitary–adrenal (HPA) axis dysregulation, such as mental disorders. This study explores novel ligands beyond mifepristone for their potential to modulate GR with improved efficacy and safety. By investigating these interactions, we seek to identify new pharmacotherapeutic options for stress-related mental illness. Methods: The ligands asoprisnil, campestanol, and stellasterol were selected based on structural similarities to mifepristone (reference ligand) and evaluated for pharmacological and ADME (absorption, distribution, metabolism, and excretion) properties using the SwissADME database. Molecular docking with AutoDock 4.2.6 and molecular dynamics simulations were performed to investigate ligand–protein interactions with the human glucocorticoid receptor, and binding free energies were calculated using MMPBSA. Results: Pharmacokinetic analysis revealed that asoprisnil exhibited high gastrointestinal absorption and obeyed Lipinski’s rule, while mifepristone crossed the blood–brain barrier. Toxicological predictions showed that mifepristone was active for neurotoxicity and immunotoxicity, while asoprisnil, campestanol, and stellasterol displayed lower toxicity profiles. Asoprisnil demonstrated the highest stability in molecular dynamics simulations, with the highest negative binding energy of −62.35 kcal/mol, when compared to mifepristone, campestanol, and stellasterol, with binding energies of −57.08 kcal/mol, −49.99 kcal/mol, and −46.69 kcal/mol, respectively. Conclusion: This makes asoprisnil a potentially favourable therapeutic candidate compared to mifepristone. However, further validation of asoprisnil’s interaction, efficacy, and safety in stress-related mental disorders through experimental studies and clinical trials is needed.